CHARACTERISING INSTITUTIONAL PRACTICES FOR GREEN SKILLS INTEGRATION IN MALAYSIAN TVET HIGHER EDUCATION - Ibrahim, Nooriza; Abdul Rahim, Zulhasni; Othman, Nor Shahima; Iqbal, Muhammad Saqib; Hisham, Fara Diba Badrul (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
The global shift towards sustainability underscores the imperative for educational systems to integrate green skills, encompassing environmental literacy, ethical decision-making, systems thinking, green innovation, and sustainable leadership. Technical and vocational education and training (TVET) institutions in Malaysia are the central platforms that foster these competencies. This qualitative exploratory study aims to characterise institutional practices integrating green skills at two prominent Malaysian TVET higher education institutions: Kolej Komuniti Kuala Langat (KKKL) and Politeknik Nilai. Using a systematic document analysis of 25 institutional artefacts from 2021 to 2024, guided by the Code of Practice for TVET Programme Accreditation (COPTPA), UNESCO’s Education for Sustainable Development (ESD) competencies, and the International Labour Organization’s (ILO) Green Skills Framework, this study identifies five core green skill domains: environmental literacy, sustainability-oriented cognitive skills, practical green work skills, green entrepreneurship, and ethical professionalism. Institutional practices differ significantly, with KKKL emphasising digital and technical integration, including smart energy systems and automation, whereas Politeknik Nilai prioritises community-based environmental literacy and experiential co-curricular engagement. This research provides actionable insights into developing a coherent and scalable national framework for systematically embedding green skills in Malaysia’s TVET higher education landscape.